THE EFFECTIVENESS OF ALENDRONATE SODIUM AND CALCITRIOL COMBINATION THERAPY IN POSTMENOPAUSAL OSTEOPOROSIS - Erhan Arif Öztürk; Haydar Gök; Peyman Yalçın (Archives of Rheumatology, 2005)
The aim of this study was to investigate the efficacy of alendronate sodium and calcitriol combination therapy on bone density and bone turnover in the treatment of postmenopausal osteoporosis. 540 women between 45-70 years of age were enrolled for assessment. Among them, 200 patients who were suitable according to medical history, physical examination, laboratory parameters and bone mineral density (BMD) measurements were recruited and randomized into 4 seperate treatment groups. The first group was treated with 10 mg/day alendronate sodium and 0.25 mcgx2/day calcitriol, the second group with 10 mg/day alendronate sodium, the third group with calcitriol 0.25 mcgx2/day, and fourth group with 1000 mg/day calcium alone for 2 years. The first three groups were also given 1000 mg/day calcium. Patents were assessed at baseline and 6 months intervals. Markers of bone formation and resorption were measured at 6 months intervals. Measurement of BMD values were done at the onset and at the end of first and second year. We concluded that alendronate sodium and calcitriol combination therapy was more effective in increasing the BMDs of the lumbar spine and hip and decreasing the bone turnover in patients with postmenopausal osteoporosis.